Cloud-assisted rendering support for mobile online gaming (Part F) - Bi, Ran (2016)
Combining gaming industry and cloud industry is the new trend in the IT industry. This Online Gaming System is a next-generation product in the gaming industry that inherits useful features from the cloud industry. The objective for this system is to allow a large pool of games to be playable on any kind of internet connected devices while avoiding issues like application compatibility and low performance. However, in the existing system, problems such as metadata conflict limit the system’s performance. Consequentially, such a system is unable to meet the objective, which results in poor gaming experience.